2020
DOI: 10.1021/acs.jafc.9b07880
|View full text |Cite
|
Sign up to set email alerts
|

Review of the Reproductive Toxicity of T-2 Toxin

Abstract: T-2 toxin, an inevitable environmental pollutant, is the most toxic type A trichothecene mycotoxin. Reproductive disruption is a key adverse effect of T-2 toxin. Herein, this paper reviews the reproductive toxicity of T-2 toxin and its mechanisms in male and female members of different species. The reproductive toxicity of T-2 toxin is evidenced by decreased fertility, disrupted structures and functions of reproductive organs, and loss of gametogenesis in males and females. T-2 toxin disrupts the reproductive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(29 citation statements)
references
References 76 publications
0
23
0
Order By: Relevance
“…The T-2 toxin is another major Fusarium mycotoxin contaminating crops [ 123 ]. In pregnant animals, the T-2 toxin induces placental lesions, embryotoxicity and abnormal development of offspring [ 123 , 124 ].…”
Section: Mechanisms Of Oxidative Stress Induction By Environmental Pollutantsmentioning
confidence: 99%
See 1 more Smart Citation
“…The T-2 toxin is another major Fusarium mycotoxin contaminating crops [ 123 ]. In pregnant animals, the T-2 toxin induces placental lesions, embryotoxicity and abnormal development of offspring [ 123 , 124 ].…”
Section: Mechanisms Of Oxidative Stress Induction By Environmental Pollutantsmentioning
confidence: 99%
“…The T-2 toxin is another major Fusarium mycotoxin contaminating crops [ 123 ]. In pregnant animals, the T-2 toxin induces placental lesions, embryotoxicity and abnormal development of offspring [ 123 , 124 ]. It has been shown that the T-2 toxin induces OS in placenta; however, its precise mode of action remains to be explored [ 125 ].…”
Section: Mechanisms Of Oxidative Stress Induction By Environmental Pollutantsmentioning
confidence: 99%
“…T-2 is the most toxic type A trichothecene mycotoxin, it is an environmental contaminant. A new report shows that reproductive disruption is a key adverse effect of T-2 toxin (Yang et al, 2020). Therefore, detection of T-2 indicated the relatively high health risk of Fusarium contamination in dried fish.…”
Section: Mycotoxin Contamination In Dried Fishmentioning
confidence: 99%
“…1 T-2 toxin is one of the most toxic trichothecene mycotoxins and causes multiple toxic effects, including immune dysregulation, neurotoxicity, and reproductive toxicity. [2][3][4] It is a wellknown RNA, DNA, and protein synthesis inhibitor, that exerts toxic effects by activating several signaling pathways, such as the mitogen-activated protein kinase (MAPK) and Janus kinase/signal transducer and activator of transcription (JAK/STAT) pathways by targeting mitochondria, ribosomes and the endoplasmic reticulum. 3,5,6 Interestingly, an increasing number of studies have revealed that T-2 toxin can selectively upregulate a group of mRNAs and proteins involved in inflammatory responses, metabolic pathways, and signal transduction to mediate T-2 toxininduced cytotoxicity, including DNA damage, apoptosis, and growth inhibition.…”
Section: Introductionmentioning
confidence: 99%
“…Mycotoxins are toxic secondary metabolites produced by fungi that usually cause food contamination and lead to mycotoxicosis in farm animals and humans 1 . T‐2 toxin is one of the most toxic trichothecene mycotoxins and causes multiple toxic effects, including immune dysregulation, neurotoxicity, and reproductive toxicity 2‐4 . It is a well‐known RNA, DNA, and protein synthesis inhibitor, that exerts toxic effects by activating several signaling pathways, such as the mitogen‐activated protein kinase (MAPK) and Janus kinase/signal transducer and activator of transcription (JAK/STAT) pathways by targeting mitochondria, ribosomes and the endoplasmic reticulum 3,5,6 .…”
Section: Introductionmentioning
confidence: 99%